High-stability in-situ crystallization catalyst as well as preparation method and application thereof

Through multi-step process treatment, the NaY zeolite silicon-aluminum ratio and crystallinity of the heavy oil catalytic cracking catalyst are improved, the problem of insufficient activity stability in the prior art is solved, and the efficient performance of the catalyst in the treatment of inferior raw materials is achieved.

CN119819353APending Publication Date: 2025-04-15WEIFANG ZHENGXUAN RARE EARTH CATALYTIC MATERIALS CO LTD

Patent Information

Application Number
CN202510314654.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-03-18
Publication Date
2025-04-15

AI Technical Summary

Technical Problem

In the prior art, the NaY zeolite silicon-aluminum ratio of heavy oil catalytic cracking catalyst is relatively low, resulting in insufficient hydrothermal activity stability and cannot meet the demand for treating inferior raw materials.

Method used

Kaolin microspheres were prepared by mixing kaolin with silica-aluminum activator, dispersant and other substances, spray-drying, and kaolin microspheres were improved through multiple calcination and in-situ crystallization synthesis reactions, and finally, a high-stable in-situ crystallization catalyst was prepared through ammonium salt, rare earth exchange and modification treatment.

Benefits of technology

The silicon-aluminum ratio and crystallinity of the catalyst are significantly improved, its catalytic performance and stability are enhanced, and it can show strong heavy oil conversion and anti-metal pollution capabilities in heavy oil catalytic cracking, and the total liquid is high.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119819353A_ABST
    Figure CN119819353A_ABST
Patent Text Reader

Abstract

The invention provides a high-stability in-situ crystallization catalyst as well as a preparation method and application thereof, and belongs to the technical field of oil refining catalysts. The preparation method comprises the following steps: firstly preparing kaolin microspheres, then roasting the kaolin microspheres into high soil balls and partial soil balls, and mixing the high soil balls and partial soil balls with a silicon source, sodium hydroxide, a seed crystal and a silicon-aluminum activator for in-situ crystallization, so that not only is the activation degree of silicon dioxide in kaolin promoted, but also the timely insertion of active silicon species into a NaY zeolite skeleton in the crystallization process is accelerated, and the activity of the NaY zeolite is improved. The high-stability in-situ crystallization catalyst is prepared by carrying out ammonium salt and rare earth exchange, roasting and phosphorus or boron modification treatment on the crystallized microspheres, and has the characteristics of strong heavy oil conversion and metal pollution resistance and high total liquid yield when being used for catalyzing heavy oil cracking.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of oil refining catalysts, and in particular relates to a high-stability in-situ crystallization catalyst and a preparation method and application thereof. Background Art

[0002] In-situ crystallized catalytic cracking catalysts play an important role in the deep conversion process of heavy oil due to their well-developed pore structure, good hydrothermal stability, and strong resistance to metal pollution. This type of catalyst is made by mixing kaolin-based clay, beating it, spraying it to form microspheres, and synthesizing NaY zeolite through high-temperature activation and hydrothermal treatment, and then undergoing ion exchange, filtration, roasting and other processes. As the processing raw materials of some domestic refineries become heavier and inferior, the content of heavy metals such as vanadium and nickel, as well as colloids and asphaltene has increased sharply, which has put forward higher requirements on the performance of heavy oil catalytic cracking catalysts. At present, a prominent problem in the preparation of in-situ crystallized heavy oil catalytic cracking catalysts is that the silicon-aluminum ratio of the synthesized NaY zeolite is low, resulting in its hydrothermal activity and stability not being able to meet the needs of catalytic devices for processing inferior raw materials.

[0003] Therefore, how to increase the silicon-to-aluminum ratio of NaY zeolite and simultaneously improve its catalytic performance has become a difficult problem in the prior art. Summary of the invention

[0004] The purpose of the present invention is to provide a high-stability in-situ crystallization catalyst and its preparation method and application. The catalyst provided by the present invention has a high silicon-aluminum ratio and has excellent catalytic performance and stability.

[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions: The present invention provides a method for preparing a high-stability in-situ crystallization catalyst, comprising the following steps: (1) Mixing kaolin with water, a silicon-aluminum activator and a dispersant, and spray drying to obtain kaolin microspheres; (2) subjecting part of the kaolin microspheres obtained in step (1) to a first calcination to obtain kaolin microspheres; (3) subjecting the remaining kaolin microspheres obtained in step (1) to a second calcination to obtain kaolin microspheres; (4) mixing the high-soil balls obtained in step (2) and the partial-soil balls obtained in step (3), water, a silicon source, a sodium hydroxide solution, a seed crystal and a silicon-alumina activator, and performing an in-situ crystallization synthesis reaction to obtain NaY zeolite crystallized microspheres; (5) mixing the NaY zeolite crystallized microspheres obtained in step (4) with ammonium salt and water to perform ammonium salt exchange to obtain ammonium salt exchange microspheres; (6) mixing the ammonium salt exchange microspheres obtained in step (5) with a rare earth salt and water, and sequentially performing a first rare earth exchange and a third calcination to obtain primary rare earth exchange microspheres; (7) mixing the primary rare earth exchange microspheres obtained in step (6) with rare earth salt and water, and sequentially performing a second rare earth exchange and a fourth calcination to obtain secondary rare earth exchange microspheres; (8) The secondary rare earth exchange microspheres obtained in step (7), water and a phosphorus compound or a boron compound are mixed and modified to obtain a high-stability in-situ crystallization catalyst.

[0006] Preferably, in step (1), the mass ratio of kaolin, silica-alumina activator and dispersant is 100:(0.5-12):(2-12).

[0007] Preferably, in step (2), the temperature of the first calcination is 900-1100° C., and the time of the first calcination is 0.5-5 h.

[0008] Preferably, in the step (3), the temperature of the second calcination is 700-880° C., and the time of the second calcination is 0.5-5 h.

[0009] Preferably, the temperature of the in-situ crystallization synthesis reaction in step (4) is 90-110° C., and the time of the in-situ crystallization synthesis reaction is 16-40 h.

[0010] Preferably, in step (5), the pH value of the ammonium salt exchange is 2.5-4, the temperature of the ammonium salt exchange is 30-100° C., and the time of the ammonium salt exchange is 0.5-4 h.

[0011] Preferably, in step (6), the pH value of the first rare earth exchange is 3-5, the temperature of the first rare earth exchange is 30-100° C., and the time of the first rare earth exchange is 0.5-4 h.

[0012] Preferably, the pH value of the modification treatment in step (8) is 2.5-4, the temperature of the modification treatment is 40-100° C., and the time of the modification treatment is 0.5-4 h.

[0013] The present invention also provides a high-stability in-situ crystallization catalyst prepared by the preparation method described in the above technical solution.

[0014] The present invention also provides the use of the high-stability in-situ crystallization catalyst described in the above technical solution in heavy oil catalytic cracking.

[0015] The present invention provides a method for preparing a high-stability in-situ crystallization catalyst, comprising the following steps: (1) mixing kaolin with water, a silicon-aluminum activator and a dispersant, and spray drying to obtain kaolin microspheres; (2) subjecting part of the kaolin microspheres obtained in the step (1) to a first roasting to obtain kaolin microspheres; (3) subjecting the remaining kaolin microspheres obtained in the step (1) to a second roasting to obtain zeolite microspheres; (4) mixing the kaolin microspheres obtained in the step (2) and the zeolite microspheres obtained in the step (3), water, a silicon source, a sodium hydroxide solution, a seed crystal and a silicon-aluminum activator, and performing an in-situ crystallization synthesis reaction to obtain NaY zeolite crystallized microspheres; (5 ) The NaY zeolite crystallized microspheres obtained in step (4) are mixed with ammonium salt and water to perform ammonium salt exchange to obtain ammonium salt exchange microspheres; (6) The ammonium salt exchange microspheres obtained in step (5) are mixed with rare earth salt and water to perform a first rare earth exchange and a third calcination in sequence to obtain primary rare earth exchange microspheres; (7) The primary rare earth exchange microspheres obtained in step (6) are mixed with rare earth salt and water to perform a second rare earth exchange and a fourth calcination in sequence to obtain secondary rare earth exchange microspheres; (8) The secondary rare earth exchange microspheres obtained in step (7), water and a phosphorus compound or a boron compound are mixed to perform a modification treatment to obtain a high-stability in-situ crystallization catalyst. The present invention first prepares kaolin microspheres, then roasts them into kaolin balls and kaolin balls, and then mixes the two with a silicon source, sodium hydroxide, a crystal seed and a silicon-aluminum activator for in-situ crystallization, which not only promotes the activation degree of silicon dioxide in kaolin, but also accelerates the crystallization process. The active silicon species are inserted into the NaY zeolite framework in time, and the silicon-aluminum ratio and crystallinity of the crystallized microspheres are improved. Then, ammonium salt, rare earth exchange and roasting and phosphorus compound modification treatment are carried out to prepare a high-stability in-situ crystallization catalyst, which has the characteristics of strong heavy oil conversion and anti-metal pollution ability and high total liquid yield when catalyzing heavy oil cracking. The results of the embodiment show that the catalyst prepared by the present invention has an activity retention rate of more than 85% after being contaminated by 8000ppm vanadium and 4000ppm nickel, and when catalyzing heavy oil cracking, the conversion rate is more than 79%, and the total liquid yield is more than 90%. BRIEF DESCRIPTION OF THE DRAWINGS

[0016] Figure 1 The XRD pattern of NaY zeolite crystallized microspheres JM-7 prepared in step (3) of Example 7; Figure 2 This is a SEM image of NaY zeolite crystallized microspheres JM-7 prepared in step (3) of Example 7; Figure 3 This is a SEM image of the surface of NaY zeolite crystallized microsphere JM-7 prepared in step (3) of Example 7; Figure 4 The XRD pattern of the crystallized microsphere DJM prepared in step (1) of comparative example 1; Figure 5This is a SEM image of the crystallized microsphere DJM prepared in step (1) of Comparative Example 1; Figure 6 This is a SEM image of the surface of the crystallized microsphere DJM prepared in step (1) of comparative example 1. DETAILED DESCRIPTION

[0017] The present invention provides a method for preparing a high-stability in-situ crystallization catalyst, comprising the following steps: (1) Mixing kaolin with water, a silicon-aluminum activator and a dispersant, and spray drying to obtain kaolin microspheres; (2) subjecting part of the kaolin microspheres obtained in step (1) to a first calcination to obtain kaolin microspheres; (3) subjecting the remaining kaolin microspheres obtained in step (1) to a second calcination to obtain kaolin microspheres; (4) mixing the high-soil balls obtained in step (2) and the partial-soil balls obtained in step (3), water, a silicon source, a sodium hydroxide solution, a seed crystal and a silicon-alumina activator, and performing an in-situ crystallization synthesis reaction to obtain NaY zeolite crystallized microspheres; (5) mixing the NaY zeolite crystallized microspheres obtained in step (4) with ammonium salt and water to perform ammonium salt exchange to obtain ammonium salt exchange microspheres; (6) mixing the ammonium salt exchange microspheres obtained in step (5) with a rare earth salt and water, and sequentially performing a first rare earth exchange and a third calcination to obtain primary rare earth exchange microspheres; (7) mixing the primary rare earth exchange microspheres obtained in step (6) with rare earth salt and water, and sequentially performing a second rare earth exchange and a fourth calcination to obtain secondary rare earth exchange microspheres; (8) The secondary rare earth exchange microspheres obtained in step (7), water and a phosphorus compound or a boron compound are mixed and modified to obtain a high-stability in-situ crystallization catalyst.

[0018] Unless otherwise specified, the present invention has no particular limitation on the sources of the raw materials, and any commercially available product or product prepared by a conventional preparation method well known to those skilled in the art may be used.

[0019] The invention mixes kaolin with water, a silicon-aluminum activator and a dispersant, and spray-dries the mixture to obtain kaolin microspheres.

[0020] In the present invention, the kaolin preferably includes at least one of ordinary kaolin and halloysite.

[0021] In the present invention, the average particle size of the kaolin is preferably 1.5-5.0 μm. In an embodiment of the present invention, the average particle size of the kaolin may specifically be 1.5 μm, 2.0 μm, 2.5 μm, 3.0 μm, 3.5 μm, 4.0 μm, 4.5 μm or 5.0 μm.

[0022] In the present invention, the molar ratio of Na2O, Al2O3, SiO2 and H2O in the silicon-aluminum activator is preferably (1-50):1:(1-60):(10-360).

[0023] In the present invention, the preparation method of the silicon-aluminum activator is preferably: a silicon source, an aluminum source and water are mixed and then aged to obtain the silicon-aluminum activator.

[0024] In the present invention, the silicon source preferably includes at least one of water glass, silica sol, white carbon black, silica gel and silicon-containing crystallization mother liquor. The present invention has no special limitation on the source of the silicon source, and commercially available products known to those skilled in the art can be used. In an embodiment of the present invention, the mass content of silicon dioxide in the water glass is 20%; the mass content of silicon dioxide in the silica sol is 30%; the mass content of silicon dioxide in the white carbon black is 99%; the silicon-containing crystallization mother liquor is a zeolite crystallization mother liquor; the mass content of silicon dioxide in the zeolite crystallization mother liquor is 12%.

[0025] In the present invention, the aluminum source preferably includes at least one of aluminum sulfate, sodium aluminate, aluminum nitrate, pseudo-boehmite, boehmite and aluminum chloride.

[0026] In the present invention, the mixing of the silicon source, the aluminum source and water is preferably performed by mixing the aluminum source and water to obtain an aluminum source solution, which is then mixed with the silicon source.

[0027] In the present invention, the mass concentration of aluminum oxide in the aluminum source solution is preferably 5-15% in terms of aluminum oxide. In an embodiment of the present invention, the mass concentration of aluminum oxide in the aluminum source solution may be specifically 5%, 6%, 7%, 8%, 9%, 10%, 12% or 15%.

[0028] In the present invention, the aging temperature is preferably 30-95° C. In an embodiment of the present invention, the aging temperature may be specifically 30° C., 40° C., 50° C., 60° C., 70° C., 80° C., 90° C. or 95° C.

[0029] In the present invention, the aging time is preferably 5 to 30 hours. In the present invention, the aging time can be specifically 5 hours, 10 hours, 15 hours, 20 hours, 25 hours or 30 hours. The present invention controls the aging temperature and time within the above range, so that the raw materials can fully react.

[0030] In the present invention, the dispersant preferably includes at least one of water glass, orthophosphoric acid, metaphosphoric acid, polyacrylamide and sodium polyacrylate.

[0031] In the present invention, the mass ratio of kaolin, silica-alumina activator and dispersant is preferably 100:(0.5-12):(2-12). In an embodiment of the present invention, the mass ratio of kaolin, silica-alumina activator and dispersant can be specifically 100:5:2, 100:3:6, 100:12:4.5 or 100:8:8.

[0032] In the present invention, the solid content of the kaolin after mixing with water, silica-alumina activator and dispersant is preferably 28-50%.

[0033] The present invention has no special limitation on the amount of water, as long as the solid content of kaolin after mixing with water, silica-alumina activator and dispersant is within the above range.

[0034] The present invention controls the mass ratio and solid content of each component within the above range, which can make the raw materials mixed more uniformly and further improve the catalytic performance of the catalyst.

[0035] In the present invention, the main particle size of the kaolin microspheres is preferably 20-150 μm, that is, the volume fraction of microspheres with a particle size of 20-150 μm accounts for ≥90%.

[0036] The present invention has no special limitation on the spray drying operation, and a technical solution well known to those skilled in the art can be used to ensure that the particle size of the kaolin microspheres is within the above range.

[0037] After obtaining the kaolin microspheres, the present invention performs a first calcination on the part of the kaolin microspheres to obtain kaolin microspheres.

[0038] In the present invention, the temperature of the first calcination is preferably 900-1100° C. In an embodiment of the present invention, the temperature of the first calcination may specifically be 900° C., 950° C., 1000° C., 1050° C. or 1100° C.

[0039] In the present invention, the time of the first calcination is preferably 0.5 to 5 hours. In an embodiment of the present invention, the time of the first calcination may be specifically 0.5 hours, 1 hour, 2 hours, 3 hours, 4 hours or 5 hours. In the present invention, the kaolinite phase in the kaolin microspheres is transformed into the spinel phase during the first calcination, and the silicon dioxide in the microspheres is activated. The present invention controls the temperature and time of the first calcination within the above range, which can further increase the active silicon dioxide content and provide sufficient active silicon source for the crystallization step.

[0040] After obtaining the kaolin balls, the present invention performs a second calcination on the remaining kaolin microballs to obtain kaolin balls.

[0041] In the present invention, the temperature of the second calcination is preferably 700-880° C. In an embodiment of the present invention, the temperature of the second calcination may specifically be 700° C., 750° C., 800° C., 850° C. or 880° C.

[0042] In the present invention, the time of the second calcination is preferably 0.5 to 5 hours. In an embodiment of the present invention, the time of the second calcination may be specifically 0.5 hours, 1 hour, 2 hours, 3 hours, 4 hours or 5 hours. In the present invention, the kaolinite phase in the kaolin microspheres is transformed into the metakaolinite phase during the second calcination process, so that the alumina in the microspheres is activated. The present invention controls the temperature and time of the second calcination within the above range, which can further increase the content of activated alumina and provide an appropriate amount of active aluminum source for the crystallization step.

[0043] After obtaining the high-clay balls and the partial clay balls, the present invention mixes the high-clay balls and the partial clay balls, water, silicon source, sodium hydroxide solution, seed crystals and silicon-aluminum activator, and performs in-situ crystallization synthesis reaction to obtain NaY zeolite crystallized microspheres.

[0044] In the present invention, the mass ratio of the high soil ball to the biased soil ball is preferably (1-7): (1-7). In an embodiment of the present invention, the mass ratio of the high soil ball to the biased soil ball can be specifically 2:3, 5.5:4.5, 7:3, 4.5:5.5, 3.5:6.5, 1:4, 3.3:6.7 or 1:3.

[0045] In the present invention, the silicon source is preferably water glass.

[0046] In the present invention, the mass content of sodium oxide in the sodium hydroxide solution is preferably 15-17%, more preferably 16%, calculated as sodium oxide.

[0047] In the present invention, the seed crystal is preferably a Y-type molecular sieve; the molar ratio of silicon dioxide to aluminum oxide in the Y-type molecular sieve is preferably ≥15.

[0048] In the present invention, the silicon-aluminum activator is preferably the same as the above-mentioned silicon-aluminum activator, which will not be described in detail here.

[0049] In the present invention, the mass ratio of the total mass of the high-clay ball and the partial clay ball, Na2O, SiO2, the seed crystal, the silicon-aluminum activator and the water in the mixed system obtained by mixing the high-clay ball and the partial clay ball, water, silicon source, sodium hydroxide, the seed crystal and the silicon-aluminum activator is preferably 100: (10-35): (15-60): (1-15): (5-45): (250-600). In the present invention, the Na2O is the total mass of sodium hydroxide (in terms of Na2O) and Na2O in water glass.

[0050] In the present invention, the mass ratio of the total mass of the high-soil ball and the partial-soil ball to the silicon source, sodium hydroxide solution, seed crystal, silicon-aluminum activator and water is preferably 100: (200-400): (150-300): (2-5): (50-100): (10-50). In an embodiment of the present invention, the mass ratio of the total mass of the high soil balls and the biased soil balls to the silicon source, sodium hydroxide solution, seed crystals, silica-alumina activator and water can be specifically: 100:210:200:2:70:20, 100:250:210:2.2:60:50, 100:350:190:4.8:90:30, 100:300:180:2.8:82:45, 100:280:240:3.5:83:30, 100:330:250:3.8:85:40, 100:320:230:4.5:78:50 or 100:270:210:4.4:79:40. The present invention controls the mass ratio of each component within the above range, which can further improve the silicon-aluminum ratio and crystallinity of the NaY zeolite crystallized microspheres, thereby improving the catalytic performance of the catalyst.

[0051] The present invention has no special limitation on the mixing operation of the high-soil balls and the partial-soil balls, water, silicon source, sodium hydroxide solution, seed crystals and silicon-aluminum activator, and the technical scheme of material mixing well known to those skilled in the art can be adopted.

[0052] In the present invention, the high-soil balls and partial-soil balls, water, silicon source, sodium hydroxide solution, seed crystals and silicon-aluminum activator are preferably aged after being mixed, and then an in-situ crystallization synthesis reaction is carried out.

[0053] In the present invention, the aging temperature is preferably 30-80° C.; the aging time is preferably 0.1-20 h.

[0054] In the present invention, the temperature of the in-situ crystallization synthesis reaction is preferably 90-110° C. In an embodiment of the present invention, the temperature of the in-situ crystallization synthesis reaction can be specifically 90° C., 95° C., 100° C., 105° C. or 110° C.

[0055] In the present invention, the time of the in-situ crystallization synthesis reaction is preferably 16 to 40 hours. In an embodiment of the present invention, the time of the in-situ crystallization synthesis reaction may be specifically 16 hours, 18 hours, 20 hours, 22 hours, 24 hours, 26 hours, 28 hours, 30 hours, 32 hours, 34 hours, 36 hours, 38 hours or 40 hours. The present invention controls the temperature and time of the in-situ crystallization synthesis reaction within the above range, so that the reaction can be fully carried out, further improve the silicon-aluminum ratio and crystallinity of the NaY zeolite crystallized microspheres, and then improve the catalytic performance of the catalyst.

[0056] After the in-situ crystallization synthesis reaction, the present invention preferably filters, washes and dries the product of the in-situ crystallization synthesis reaction in sequence to obtain NaY zeolite crystallized microspheres.

[0057] The present invention has no special limitation on the filtering, washing and drying operations, and the technical solutions well known to those skilled in the art can be adopted.

[0058] In the present invention, the mass content of NaY zeolite in the NaY zeolite crystallized microspheres is preferably 50-70%; the amount ratio of silicon to aluminum in the NaY zeolite crystallized microspheres is preferably 5.0-6.1.

[0059] After obtaining the NaY zeolite crystallized microspheres, the present invention mixes the NaY zeolite crystallized microspheres with ammonium salt and water to perform ammonium salt exchange to obtain ammonium salt exchanged microspheres.

[0060] In the present invention, the ammonium salt preferably includes at least one of ammonium chloride, ammonium sulfate, ammonium nitrate and ammonium phosphate.

[0061] In the present invention, the mass ratio of the ammonium salt to the NaY zeolite crystallized microspheres is preferably 0.15 to 0.6. In an embodiment of the present invention, the mass ratio of the ammonium salt to the NaY zeolite crystallized microspheres may be specifically 0.15, 0.18, 0.2, 0.25, 0.3, 0.35, 0.4, 0.45, 0.5, 0.55 or 0.6.

[0062] In the present invention, the volume ratio of the water to the mass ratio of the NaY zeolite crystallized microspheres is preferably 3 to 10 L / g. In the present invention, the volume ratio of the water to the mass ratio of the NaY zeolite crystallized microspheres may specifically be 3 L / g, 4 L / g, 5 L / g, 6 L / g, 7 L / g, 8 L / g, 9 L / g or 10 L / g.

[0063] In the present invention, the pH value of the ammonium salt exchange is preferably 2.5 to 4. In an embodiment of the present invention, the pH value of the ammonium salt exchange can be specifically 2.5, 3.0, 3.5 or 4.0.

[0064] In the present invention, the temperature of the ammonium salt exchange is preferably 30-100° C. In an embodiment of the present invention, the temperature of the ammonium salt exchange may be specifically 30° C., 40° C., 50° C., 60° C., 70° C., 80° C., 90° C. or 100° C.

[0065] In the present invention, the time for the ammonium salt exchange is preferably 0.5 to 4 hours. In an embodiment of the present invention, the time for the ammonium salt exchange can be specifically 0.5 hours, 1 hour, 1.5 hours, 2 hours, 2.5 hours, 3 hours, 3.5 hours or 4 hours.

[0066] The present invention controls the dosage of each component, the reaction temperature and the reaction time within the above ranges, so that the reaction can proceed fully.

[0067] After the ammonium salt exchange is completed, the present invention preferably filters and washes the ammonium salt exchange product in sequence to obtain ammonium salt exchange microspheres.

[0068] The present invention has no special limitation on the filtering and washing operations, and the filtering and washing technical solutions well known to those skilled in the art can be adopted.

[0069] After obtaining the ammonium salt exchange microspheres, the present invention mixes the ammonium salt exchange microspheres with rare earth salt and water, and sequentially performs a first rare earth exchange and a third calcination to obtain primary rare earth exchange microspheres.

[0070] In the present invention, the rare earth salt preferably includes at least one of rare earth hydrochlorides, rare earth nitrates and rare earth carbonates; the rare earth in the rare earth salt preferably includes at least one of La, Ce, Pr, Y and Sc.

[0071] In the present invention, the rare earth in the rare earth salt is preferably La and Ce, and the mass ratio of lanthanum oxide to cerium oxide in the rare earth salt is preferably (2-3):1, calculated as lanthanum oxide and cerium oxide.

[0072] In the present invention, the rare earth salt is calculated as rare earth oxide, and the mass ratio of the rare earth oxide to the NaY zeolite crystallized microspheres is preferably 0.02 to 0.06. In an embodiment of the present invention, the mass ratio of the rare earth oxide to the NaY zeolite crystallized microspheres can be specifically 0.02, 0.03, 0.04, 0.05 or 0.06.

[0073] In the present invention, the ammonium salt exchange microspheres are preferably mixed with the rare earth salt and water by mixing the rare earth salt and part of the water to obtain a rare earth salt solution, which is then mixed with the ammonium salt exchange microspheres and the remaining water.

[0074] In the present invention, the rare earth salt is calculated as rare earth oxide, and the concentration of the rare earth oxide in the rare earth salt solution is preferably 240-270 g / L. The present invention has no special limitation on the amount of the water, as long as the concentration of the rare earth oxide in the rare earth salt solution is within the above range.

[0075] In the present invention, the volume ratio of the water to the mass ratio of the NaY zeolite crystallized microspheres is preferably 3 to 10 L / g. In the present invention, the volume ratio of the water to the mass ratio of the NaY zeolite crystallized microspheres may specifically be 3 L / g, 4 L / g, 5 L / g, 6 L / g, 7 L / g, 8 L / g, 9 L / g or 10 L / g.

[0076] In the present invention, the pH value of the first rare earth exchange is preferably 3 to 5. In an embodiment of the present invention, the pH value of the first rare earth exchange can be specifically 3, 3.5, 4, 4.5 or 5.

[0077] In the present invention, the temperature of the first rare earth exchange is preferably 30-100° C. In an embodiment of the present invention, the temperature of the first rare earth exchange can be specifically 30° C., 40° C., 50° C., 60° C., 70° C., 80° C., 90° C. or 100° C.

[0078] In the present invention, the time for the first rare earth exchange is preferably 0.5 to 4 hours. In an embodiment of the present invention, the time for the first rare earth exchange can be specifically 0.5 hours, 1 hour, 1.5 hours, 2 hours, 2.5 hours, 3 hours, 3.5 hours or 4 hours.

[0079] The present invention controls the dosage of each component, the reaction temperature and the reaction time within the above ranges, so that the reaction can proceed fully.

[0080] After the first rare earth exchange is completed, the present invention preferably filters and washes the product of the first rare earth exchange in sequence, and then performs a third calcination.

[0081] The present invention has no special limitation on the filtering and washing operations, and the filtering and washing technical solutions well known to those skilled in the art can be adopted.

[0082] In the present invention, the temperature of the third calcination is preferably 450-700° C. In an embodiment of the present invention, the temperature of the third calcination may specifically be 450° C., 500° C., 550° C., 600° C., 650° C. or 700° C.

[0083] In the present invention, the third calcination time is preferably 0.5 to 4 hours. In an embodiment of the present invention, the third calcination time can be specifically 0.5 hours, 1 hour, 1.5 hours, 2 hours, 2.5 hours, 3 hours, 3.5 hours or 4 hours.

[0084] In the present invention, the third calcination is preferably carried out under air or water vapor conditions. In the present invention, the volume percentage of the water vapor is preferably 10 to 50%. The present invention controls the parameters such as the amount of each component, reaction temperature and time within the above range, which can allow more rare earths to be exchanged and further improve the catalytic performance of the catalyst.

[0085] After obtaining the primary rare earth exchange microspheres, the present invention mixes the primary rare earth exchange microspheres with rare earth salt and water, and sequentially performs a second rare earth exchange and a fourth calcination to obtain secondary rare earth exchange microspheres.

[0086] In the present invention, the rare earth salt preferably includes at least one of rare earth hydrochlorides, rare earth nitrates and rare earth carbonates; the rare earth in the rare earth salt preferably includes at least one of La, Ce, Pr, Y and Sc.

[0087] In the present invention, the rare earth in the rare earth salt is preferably La and Ce, and the mass ratio of lanthanum oxide to cerium oxide in the rare earth salt is preferably (2-3):1, calculated as lanthanum oxide and cerium oxide.

[0088] In the present invention, the rare earth salt is calculated as rare earth oxide, and the mass ratio of the rare earth oxide to the NaY zeolite crystallized microspheres is preferably 0.02 to 0.06. In an embodiment of the present invention, the mass ratio of the rare earth oxide to the NaY zeolite crystallized microspheres can be specifically 0.02, 0.03, 0.04, 0.05 or 0.06.

[0089] In the present invention, the mixing of the primary rare earth exchange microspheres with the rare earth salt and water is preferably: the rare earth salt is mixed with part of the water to obtain a rare earth salt solution, which is then mixed with the primary rare earth exchange microspheres and the remaining water.

[0090] In the present invention, the rare earth salt is calculated as rare earth oxide, and the concentration of the rare earth oxide in the rare earth salt solution is preferably 240-270 g / L. The present invention has no special limitation on the amount of the water, as long as the concentration of the rare earth oxide in the rare earth salt solution is within the above range.

[0091] In the present invention, the volume ratio of the water to the mass ratio of the NaY zeolite crystallized microspheres is preferably 3 to 10 L / g. In the present invention, the volume ratio of the water to the mass ratio of the NaY zeolite crystallized microspheres may specifically be 3 L / g, 4 L / g, 5 L / g, 6 L / g, 7 L / g, 8 L / g, 9 L / g or 10 L / g.

[0092] In the present invention, the pH value of the second rare earth exchange is preferably 3 to 5. In an embodiment of the present invention, the pH value of the second rare earth exchange can be specifically 3, 3.5, 4, 4.5 or 5.

[0093] In the present invention, the temperature of the second rare earth exchange is preferably 30-100° C. In an embodiment of the present invention, the temperature of the second rare earth exchange can be specifically 30° C., 40° C., 50° C., 60° C., 70° C., 80° C., 90° C. or 100° C.

[0094] In the present invention, the second rare earth exchange time is preferably 0.5 to 4 hours. In an embodiment of the present invention, the second rare earth exchange time can be specifically 0.5 hours, 1 hour, 1.5 hours, 2 hours, 2.5 hours, 3 hours, 3.5 hours or 4 hours.

[0095] The present invention controls the dosage of each component, the reaction temperature and the reaction time within the above ranges, so that the reaction can proceed fully.

[0096] After the second rare earth exchange is completed, the present invention preferably filters and washes the product of the second rare earth exchange in sequence, and then performs a fourth calcination.

[0097] The present invention has no special limitation on the filtering and washing operations, and the filtering and washing technical solutions well known to those skilled in the art can be adopted.

[0098] In the present invention, the temperature of the fourth calcination is preferably 500-750° C. In an embodiment of the present invention, the temperature of the fourth calcination may specifically be 500° C., 550° C., 600° C., 650° C., 700° C. or 750° C.

[0099] In the present invention, the fourth calcination time is preferably 0.5 to 4 hours. In an embodiment of the present invention, the fourth calcination time can be specifically 0.5 hours, 1 hour, 1.5 hours, 2 hours, 2.5 hours, 3 hours, 3.5 hours or 4 hours.

[0100] In the present invention, the fourth calcination is preferably carried out under air or water vapor conditions. In the present invention, the volume percentage of the water vapor is preferably 10 to 50%. The present invention controls the parameters such as the amount of each component, reaction temperature and time within the above range, which can allow more rare earths to be exchanged and further improve the catalytic performance of the catalyst.

[0101] After obtaining the secondary rare earth exchange microspheres, the present invention mixes the secondary rare earth exchange microspheres, water and a phosphorus compound or a boron compound, performs a modification treatment, and obtains a high-stability in-situ crystallization catalyst.

[0102] In the present invention, the phosphorus compound preferably includes at least one of ammonium phosphate, ammonium hydrogen phosphate, ammonium dihydrogen phosphate, pyrophosphoric acid and metaphosphoric acid.

[0103] In the present invention, the boron compound preferably includes at least one of boric acid and ammonium borate.

[0104] In the present invention, the mass ratio of the phosphorus compound or boron compound to the NaY zeolite crystallized microspheres is preferably 0.005 to 0.2. In an embodiment of the present invention, the mass ratio of the phosphorus compound or boron compound to the NaY zeolite crystallized microspheres can be specifically 0.005, 0.01, 0.05, 0.1, 0.15 or 0.2.

[0105] In the present invention, the volume ratio of the water to the mass ratio of the NaY zeolite crystallized microspheres is preferably 3 to 9 L / g. In the present invention, the volume ratio of the water to the mass ratio of the NaY zeolite crystallized microspheres can be specifically 3 L / g, 4 L / g, 5 L / g, 6 L / g, 7 L / g, 8 L / g or 9 L / g.

[0106] In the present invention, the pH value of the modification treatment is preferably 2.5 to 4. In an embodiment of the present invention, the pH value of the modification treatment may specifically be 2.5, 3, 3.5 or 4.

[0107] In the present invention, the temperature of the modification treatment is preferably 40-100° C. In an embodiment of the present invention, the temperature of the modification treatment may specifically be 40° C., 50° C., 60° C., 70° C., 80° C., 90° C. or 100° C.

[0108] In the present invention, the time of the modification treatment is preferably 0.5 to 4 hours. In an embodiment of the present invention, the time of the modification treatment may be specifically 0.5 hours, 1 hour, 1.5 hours, 2 hours, 2.5 hours, 3 hours, 3.5 hours or 4 hours. The present invention controls the amount of each component, the reaction temperature and the time within the above range, so that the modification treatment can be more sufficient and the catalytic performance of the catalyst can be further improved.

[0109] After the modification treatment is completed, the present invention preferably filters, washes and dries the modified product in sequence to obtain a high-stability in-situ crystallization catalyst.

[0110] The present invention has no special limitation on the filtering, washing and drying operations, and the technical solutions well known to those skilled in the art can be adopted.

[0111] The invention first prepares kaolin microspheres, then roasts them into kaolin balls and zeolite balls, and then mixes the two with a silicon source, sodium hydroxide, a crystal seed and a silicon-aluminum activator for in-situ crystallization, which not only promotes the activation degree of silicon dioxide in kaolin, but also accelerates the timely insertion of active silicon species into the NaY zeolite framework during the crystallization process, thereby improving the silicon-aluminum ratio and crystallinity of the crystallized microspheres, and then performs ammonium salt, rare earth exchange and roasting and phosphorus or boron modification treatment. After the ammonium salt, rare earth exchange and roasting and modification treatment, the micro-reaction activity and hydrothermal stability thereof are greatly improved, the catalytic performance of the catalyst is further improved, and the process parameters such as the amount of each component, reaction temperature and time are controlled to prepare a high-stability in-situ crystallization catalyst.

[0112] The present invention also provides a high-stability in-situ crystallization catalyst prepared by the preparation method described in the above technical solution.

[0113] The present invention also provides the use of the high-stability in-situ crystallization catalyst described in the above technical solution in heavy oil catalytic cracking.

[0114] The high-stability in-situ crystallization catalyst of the present invention can be used for processing various raw materials, including paraffin-based, cycloalkyl-based, intermediate-based wax oils and blended residual oil raw materials.

[0115] In the present invention, the temperature of the catalytic cracking is preferably 400-700°C, more preferably 450-650°C; during the catalytic cracking, the mass ratio of the catalyst to the heavy oil is preferably 3-25, more preferably 4-22.

[0116] The catalyst prepared by the invention has excellent catalytic performance, and has the characteristics of strong heavy oil conversion and metal pollution resistance and high total liquid yield when catalyzing heavy oil cracking.

[0117] The technical solutions in the present invention will be described clearly and completely below in conjunction with the embodiments of the present invention. Obviously, the described embodiments are only a part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0118] The specifications, compositions or preparation methods of the raw materials in the embodiments and comparative examples are as follows: Kaolin, solid content 85.8%, Fe2O3 0.3wt%, TiO2 0.2wt%, average particle size 3.5μm.

[0119] Halloysite (haywater kaolinite), solid content 86.4%, Fe2O3 1.1wt%, TiO2 2.5wt%, average particle size 2.1μm.

[0120] 1# seed crystal, USY silicon-aluminum ratio is 25; 2# seed crystal, USY silicon-aluminum ratio is 15.

[0121] Zeolite crystallization mother liquor, SiO2 12wt%.

[0122] Directing agent: 15SiO2:Al2O3:15Na2O:320H2O (ratio of moles of substance).

[0123] Water glass, SiO2 content 20wt%; silica sol, SiO2 content 30wt%; white carbon black, SiO2 99wt%.

[0124] Sodium aluminate, Al2O3 content 7wt%, aluminum sulfate, Al2O3 content 12wt%, sodium hydroxide solution, Na2O content 16wt%.

[0125] Hydrochloric acid 36wt%; phosphoric acid 85wt%; phosphorous acid, chemically pure; sulfuric acid 98wt%.

[0126] The rare earth chloride solution, calculated as rare earth oxide, has a rare earth oxide concentration of 265 g / L; the rare earth nitric acid solution, calculated as rare earth oxide, has a rare earth oxide concentration of 242 g / L.

[0127] The main testing methods are: NaY zeolite content: determined according to RIPP146-90 standard method and obtained from relative crystallinity.

[0128] NaY zeolite silicon-aluminum ratio (SiO2 / Al2O3): First determine the NaY zeolite unit cell constant a o , measured according to RIPP145-90 standard method, and then calculated according to the following formula: SiO2 / Al2O3 (molar ratio) = 2×(25.858-a o ) / (a o -24.191).

[0129] Kaolinite content: XRD diffraction method.

[0130] Elemental composition: XRF fluorescence method.

[0131] Solid content: ignition method, 800℃ / 1h.

[0132] Average particle size: laser particle size analyzer method.

[0133] Morphology: SEM electron microscopy analysis.

[0134] 1000 mL of water glass (SiO2 20 wt%) and 300 mL of aluminum sulfate (Al2O3 10 wt%) aqueous solution were mixed evenly and reacted at 50 °C for 15 h to obtain the silica-alumina activator SA-1. The molar ratio of Na2O, Al2O3, SiO2 and H2O was 5.1:1:13:196.

[0135] 800 mL of silica sol (SiO2 30 wt%) and 500 mL of sodium aluminate (Al2O3 7 wt%) aqueous solution were mixed evenly and reacted at 70 °C for 10 h to obtain silica-alumina activator SA-2. The molar ratio of Na2O, Al2O3, SiO2 and H2O was 4.9:1:10.6:29.

[0136] 1500mL of zeolite crystallization mother liquor (SiO2 12w%) and 250mL of aluminum sulfate (Al2O3 12w%) aqueous solution were mixed evenly and reacted at 90℃ for 5h to obtain silicon-aluminum activator SA-3. The molar ratio of Na2O, Al2O3, SiO2 and H2O was 4:1:7.1:197.

[0137] Example 1 The preparation method of the high-stability in-situ crystallization catalyst is as follows: (1) 5000 g of kaolin (calcined base), water glass, silica-alumina activator SA-1 and water (the mass ratio of kaolin to water glass and silica-alumina activator SA-1 is 100:2:5) are prepared into a kaolin slurry with a solid content of 35%, and the slurry is spray-dried to obtain 4900 g of kaolin microspheres with a main particle size of 20-150 μm, which are recorded as RM1; (2) The kaolin microspheres were calcined at 940 °C for 3 h to obtain kaolin microspheres, which were designated as GM1-1. The kaolin microspheres were calcined at 760 °C for 3.5 h to obtain PM1-1. (3) Mix the kaolinite balls and the zeolite balls with water, water glass, sodium hydroxide solution (Na2O 16wt%), 1# seed crystals and alumina-silica activator SA-1 (the mass ratio of the kaolinite balls and the zeolite balls is 1:1.5, and the mass ratio of the total mass of the kaolinite balls and the zeolite balls, water glass, sodium hydroxide solution, 1# seed crystals, alumina-silica activator SA-1 and water is 100:210:200:2:70:20), and perform in-situ crystallization synthesis reaction at 98°C for 27h, filter, wash and dry to obtain NaY zeolite crystallized microspheres, recorded as JM-1; (4) 1000 g of NaY zeolite crystallized microspheres, 390 g of ammonium chloride and 5000 g of deionized water were mixed (the mass ratio of ammonium chloride to NaY zeolite crystallized microspheres was 0.39, and the volume ratio of water to the mass ratio of NaY zeolite crystallized microspheres was 5 L / g), the pH value was adjusted to 3.2, exchange was performed at 95 °C for 1.5 h, and a "one-cross" filter cake was obtained after filtering and washing; deionized water and rare earth chloride aqueous solution (the concentration of rare earth oxides in the rare earth chloride aqueous solution was 265 g / L, and the concentration of rare earth oxides and NaY The mass ratio of zeolite crystallized microspheres is 0.05, the rare earth elements in rare earth chloride are lanthanum and cerium, calculated as lanthanum oxide and cerium oxide, the mass ratio of lanthanum oxide and cerium oxide in rare earth chloride is 2:1, the total volume of water in deionized water and rare earth chloride aqueous solution and the mass ratio of NaY zeolite crystallized microspheres is 4.5L / g), mixed evenly, adjusted to pH 3.5, exchanged at 95°C for 1h, filtered and washed to obtain a "second exchange" wet cake, calcined at 600°C for 2.5h to obtain a primary rare earth exchange microsphere, added to the primary rare earth exchange microsphere Water and rare earth chloride aqueous solution (the concentration of rare earth oxide in the rare earth chloride aqueous solution is 265g / L, the mass ratio of rare earth oxide to NaY zeolite crystallized microspheres is 0.04, the rare earth elements in the rare earth chloride are lanthanum and cerium, calculated as lanthanum oxide and cerium oxide, the mass ratio of lanthanum oxide to cerium oxide in the rare earth chloride is 2:1, the total volume of deionized water and water in the rare earth chloride aqueous solution and the mass ratio of NaY zeolite crystallized microspheres is 4.5L / g), mixed evenly, adjusted the pH value to 3.2, exchanged at 85℃ for 1h, filtered and washed, and obtained The "three-cross" wet filter cake was calcined at 600°C for 2.5h to obtain secondary rare earth exchange microspheres; water and 100g of ammonium phosphate (the mass ratio of ammonium phosphate to NaY zeolite crystallized microspheres was 0.10, and the mass ratio of the volume of water to the mass ratio of the NaY zeolite crystallized microspheres was 4.5L / g) were added to the secondary rare earth exchange microspheres, mixed evenly, the pH value was adjusted to 2.8, and the catalyst was modified at 85°C for 1h, filtered, washed and dried to obtain a high-stability in-situ crystallized catalyst, recorded as HC-1. The rare earth oxide content was 7.1wt% and P 1.6wt% after analysis.

[0138] Example 2 The preparation method of the high-stability in-situ crystallization catalyst is as follows: (1) 5000 g of kaolin (calcined base), water glass, silica-alumina activator SA-1 and water (the mass ratio of kaolin to water glass and silica-alumina activator SA-1 is 100:2:5) are prepared into a kaolin slurry with a solid content of 35%, and the slurry is spray-dried to obtain 4900 g of kaolin microspheres with a main particle size of 20-150 μm, which are recorded as RM1; (2) The kaolin microspheres were calcined at 980°C for 1.5 h to obtain kaolin microspheres, which were designated as GM1-2; the kaolin microspheres were calcined at 800°C for 2 h to obtain PM1-2; (3) Mix the high-quality zeolite balls and the partial zeolite balls with water, water glass, sodium hydroxide solution (Na2O 16wt%), 2# seed crystals and alumina-silica activator SA-2 (the mass ratio of the high-quality zeolite balls and the partial zeolite balls is 5.5:4.5, and the mass ratio of the total mass of the high-quality zeolite balls and the partial zeolite balls, water glass, sodium hydroxide solution, 2# seed crystals, alumina-silica activator SA-2 and water is 100:250:210:2.2:60:50), and perform in-situ crystallization synthesis reaction at 98°C for 20h, filter, wash and dry to obtain NaY zeolite crystallized microspheres, recorded as JM-2; (4) 1000 g of NaY zeolite crystallized microspheres, 390 g of ammonium chloride and 5000 g of deionized water were mixed (the mass ratio of ammonium chloride to NaY zeolite crystallized microspheres was 0.39, and the volume ratio of water to the mass ratio of NaY zeolite crystallized microspheres was 5 L / g), the pH value was adjusted to 3.2, exchange was performed at 95°C for 1.5 h, and a "one-cross" filter cake was obtained after filtering and washing; deionized water and rare earth chloride aqueous solution (the concentration of rare earth oxides in the rare earth chloride aqueous solution was 265 g / L, and the concentration of rare earth oxides in the rare earth chloride aqueous solution was 265 g / L) were added to the "one-cross" filter cake. The mass ratio of oxide to NaY zeolite crystallized microspheres is 0.05, the rare earth elements in rare earth chloride are lanthanum and cerium, calculated as lanthanum oxide and cerium oxide, the mass ratio of lanthanum oxide to cerium oxide in rare earth chloride is 2:1, the total volume of water in deionized water and rare earth chloride aqueous solution and the mass ratio of NaY zeolite crystallized microspheres is 4.5L / g), mixed evenly, adjusted to pH 3.5, exchanged at 95°C for 1h, filtered and washed to obtain a "secondary exchange" wet cake, which was calcined at 600°C for 2.5h to obtain a primary rare earth exchange microsphere. Add water and rare earth chloride aqueous solution to the primary rare earth exchange microspheres (the concentration of rare earth oxide in the rare earth chloride aqueous solution is 265 g / L, the mass ratio of rare earth oxide to NaY zeolite crystallized microspheres is 0.04, the rare earth elements in the rare earth chloride are lanthanum and cerium, calculated as lanthanum oxide and cerium oxide, the mass ratio of lanthanum oxide to cerium oxide in the rare earth chloride is 2:1, the total volume of deionized water and water in the rare earth chloride aqueous solution and the mass ratio of NaY zeolite crystallized microspheres is 4.5 L / g), mix well, and adjust the pH value to 3.2, exchange at 85℃ for 1h, filter and wash to obtain a "three-cross" wet filter cake, calcine at 600℃ for 2.5h to obtain secondary rare earth exchange microspheres; add water and 100g ammonium phosphate (the mass ratio of ammonium phosphate to NaY zeolite crystallized microspheres is 0.10, and the mass ratio of the volume of water to the NaY zeolite crystallized microspheres is 4.5L / g) to the secondary rare earth exchange microspheres, mix evenly, adjust the pH value to 2.8, modify at 85℃ for 1h, filter, wash and dry to obtain a high-stability in-situ crystallization catalyst.

[0139] Example 3 The preparation method of the high-stability in-situ crystallization catalyst is as follows: (1) 5000 g of kaolin (calcined base), water glass, silica-alumina activator SA-2 and water (the mass ratio of kaolin to water glass and silica-alumina activator SA-2 is 100:6:3) are prepared into a kaolin slurry with a solid content of 45%, and the slurry is spray-dried to obtain 4700 g of kaolin microspheres with a main particle size of 20-150 μm, which are recorded as RM2; (2) The kaolin microspheres were calcined at 920°C for 3 h to obtain kaolin microspheres, which were designated as GM2-1. The kaolin microspheres were calcined at 780°C for 4 h to obtain PM2-1. (3) Mix the high-quality soil balls and the partial soil balls with water, water glass, sodium hydroxide solution (Na2O 16wt%), 1# seed crystals and alumina-silica activator SA-3 (the mass ratio of the high-quality soil balls and the partial soil balls is 7:3, and the mass ratio of the total mass of the high-quality soil balls and the partial soil balls, water glass, sodium hydroxide solution, 1# seed crystals, alumina-silica activator SA-3 and water is 100:350:190:4.8:90:30), and perform in-situ crystallization synthesis reaction at 98°C for 35h, filter, wash and dry to obtain NaY zeolite crystallized microspheres, recorded as JM-3; (4) 1000 g of NaY zeolite crystallized microspheres, 450 g of ammonium nitrate and 6500 g of deionized water were mixed (the mass ratio of ammonium nitrate to NaY zeolite crystallized microspheres was 0.45, and the volume ratio of water to the mass ratio of NaY zeolite crystallized microspheres was 6.5 L / g), the pH value was adjusted to 3.5, exchange was performed at 75 °C for 2 h, and a "one-cross" filter cake was obtained after filtering and washing; deionized water and rare earth nitrate aqueous solution (the concentration of rare earth oxides in the rare earth nitrate aqueous solution was 242 g / L, and the concentration of rare earth oxides and Na The mass ratio of Y zeolite crystallized microspheres is 0.045, the rare earth elements in rare earth nitrate are lanthanum and cerium, calculated as lanthanum oxide and cerium oxide, the mass ratio of lanthanum oxide and cerium oxide in rare earth nitrate is 2:1, the total volume of water in deionized water and rare earth nitrate aqueous solution and the mass ratio of NaY zeolite crystallized microspheres is 4.5L / g), mixed evenly, adjusted to pH 3.8, exchanged at 85℃ for 1.5h, filtered and washed to obtain a "second exchange" wet cake, calcined at 550℃ for 3h to obtain a primary rare earth exchange microsphere, in the primary rare earth exchange microsphere Add water and rare earth chloride aqueous solution (the concentration of rare earth oxide in the rare earth chloride aqueous solution is 265g / L, the mass ratio of rare earth oxide to NaY zeolite crystallized microspheres is 0.05, the rare earth elements in the rare earth chloride are lanthanum and cerium, calculated as lanthanum oxide and cerium oxide, the mass ratio of lanthanum oxide to cerium oxide in the rare earth chloride is 2:1, the total volume of deionized water and water in the rare earth chloride aqueous solution and the mass ratio of NaY zeolite crystallized microspheres is 6L / g), mix well, adjust the pH value to 3.5, exchange at 90℃ for 1h, filter and wash, and obtain The "three-cross" wet filter cake was calcined at 620°C for 2h to obtain secondary rare earth exchange microspheres; water and 120g of ammonium dihydrogen phosphate (the mass ratio of ammonium dihydrogen phosphate to NaY zeolite crystallized microspheres was 0.12, and the mass ratio of the volume of water to the NaY zeolite crystallized microspheres was 5L / g) were added to the secondary rare earth exchange microspheres, mixed evenly, the pH value was adjusted to 3.2, and the catalyst was modified at 90°C for 1h, filtered, washed and dried to obtain a high-stability in-situ crystallized catalyst, recorded as HC-2. The rare earth oxide content was 8.4wt% and P 2.7wt% after analysis.

[0140] Example 4 The preparation method of the high-stability in-situ crystallization catalyst is as follows: (1) 5000 g of kaolin (calcined base), water glass, silica-alumina activator SA-2 and water (the mass ratio of kaolin to water glass and silica-alumina activator SA-2 is 100:6:3) are prepared into a kaolin slurry with a solid content of 45%, and the slurry is spray-dried to obtain 4700 g of kaolin microspheres with a main particle size of 20-150 μm, which are recorded as RM2; (2) The kaolin microspheres were calcined at 970°C for 2 h to obtain kaolin microspheres, which were designated as GM2-2; the kaolin microspheres were calcined at 820°C for 2 h to obtain PM2-2; (3) Mix the high-quality clay balls and the partial clay balls with water, water glass, sodium hydroxide solution (Na2O 16wt%), 2# seed crystals and alumina-silica activator SA-1 (the mass ratio of the high-quality clay balls and the partial clay balls is 4.5:5.5, and the mass ratio of the total mass of the high-quality clay balls and the partial clay balls, water glass, sodium hydroxide solution, 2# seed crystals, alumina-silica activator SA-1 and water is 100:300:180:2.8:82:45), and perform in-situ crystallization synthesis reaction at 98°C for 24h, filter, wash and dry to obtain NaY zeolite crystallized microspheres, recorded as JM-4; (4) 1000 g of NaY zeolite crystallized microspheres, 450 g of ammonium chloride and 6500 g of deionized water were mixed (the mass ratio of ammonium chloride to NaY zeolite crystallized microspheres was 0.45, and the volume ratio of water to the mass ratio of NaY zeolite crystallized microspheres was 6.5 L / g), the pH value was adjusted to 3.5, and the mixture was exchanged at 75 °C for 2 h. After filtering and washing, a "one-cross" filter cake was obtained; deionized water and a rare earth nitrate aqueous solution (the concentration of rare earth oxides in the rare earth nitrate aqueous solution was 242 g / L, and the concentration of rare earth oxides in the rare earth nitrate aqueous solution was 242 g / L, and the concentration of rare earth oxides in the rare earth nitrate aqueous solution was 242 g / L) were added to the "one-cross" filter cake. The mass ratio of oxide to NaY zeolite crystallized microspheres is 0.045, the rare earth elements in rare earth nitrate are lanthanum and cerium, calculated as lanthanum oxide and cerium oxide, the mass ratio of lanthanum oxide to cerium oxide in rare earth nitrate is 2:1, the total volume of water in deionized water and rare earth nitrate aqueous solution and the mass ratio of NaY zeolite crystallized microspheres is 4.5L / g), mixed evenly, adjusted to pH 3.8, exchanged at 85°C for 1.5h, filtered and washed to obtain a "secondary exchange" wet cake, which was calcined at 550°C for 3h to obtain a primary rare earth exchange microsphere. Add water and rare earth chloride aqueous solution to the primary rare earth exchange microspheres (the concentration of rare earth oxide in the rare earth chloride aqueous solution is 265 g / L, the mass ratio of rare earth oxide to NaY zeolite crystallized microspheres is 0.05, the rare earth elements in the rare earth chloride are lanthanum and cerium, calculated as lanthanum oxide and cerium oxide, the mass ratio of lanthanum oxide to cerium oxide in the rare earth chloride is 2:1, the total volume of deionized water and water in the rare earth chloride aqueous solution and the mass ratio of NaY zeolite crystallized microspheres is 6 L / g), mix well, adjust the pH value to 3.5, Exchange at 90℃ for 1h, filter and wash to obtain a "three-cross" wet filter cake, which is calcined at 620℃ for 2h to obtain secondary rare earth exchange microspheres; add 5000g water and 120g diammonium phosphate (the mass ratio of diammonium phosphate to NaY zeolite crystallized microspheres is 0.12, and the volume of water to the mass ratio of NaY zeolite crystallized microspheres is 5L / g) to the secondary rare earth exchange microspheres), mix evenly, adjust the pH value to 3.2, modify at 90℃ for 1h, filter, wash and dry to obtain a high-stability in-situ crystallization catalyst.

[0141] Example 5 The preparation method of the high-stability in-situ crystallization catalyst is as follows: (1) 5000 g of halloysite (calcined), orthophosphoric acid, water glass, silica-alumina activator SA-3 and water (the mass ratio of halloysite to orthophosphoric acid, water glass and silica-alumina activator SA-3 is 100:1.5:3:12, and the mass ratio of the mass of halloysite, the total mass of orthophosphoric acid and water glass to the silica-alumina activator SA-3 is 100:4.5:12) are prepared into a kaolin slurry with a solid content of 38%, and spray-dried to obtain 4500 g of kaolin microspheres with a main particle size of 20-150 μm, which are recorded as RM3; (2) The kaolin microspheres were calcined at 950 °C for 2 h to obtain kaolin microspheres, which were designated as GM3-1. The kaolin microspheres were calcined at 770 °C for 3.5 h to obtain PM3-1. (3) Mix the kaolinite balls and the zeolite balls with water, water glass, sodium hydroxide solution (Na2O 16wt%), 1# seed crystals and alumina-silica activator SA-1 (the mass ratio of the kaolinite balls and the zeolite balls is 3.5:6.5, and the mass ratio of the total mass of the kaolinite balls and the zeolite balls, water glass, sodium hydroxide solution, 1# seed crystals, alumina-silica activator SA-1 and water is 100:280:240:3.5:83:30), and perform in-situ crystallization synthesis reaction at 98°C for 29h, filter, wash and dry to obtain NaY zeolite crystallized microspheres, recorded as JM-5; (4) 1000 g of NaY zeolite microspheres, 350 g of ammonium nitrate and 4500 g of deionized water were mixed (the mass ratio of ammonium nitrate to NaY zeolite microspheres was 0.35, and the volume ratio of water to the mass ratio of NaY zeolite microspheres was 4.5 L / g), the pH value was adjusted to 3.0, exchanged at 85 °C for 2 h, filtered and washed to obtain a "one-cross" filter cake; deionized water and rare earth chloride aqueous solution (the concentration of rare earth oxides in the rare earth chloride aqueous solution was 265 g / L, and the concentration of rare earth oxides and NaY zeolite microspheres was 2.5 g / L) were added to the "one-cross" filter cake. The mass ratio of the zeolite microspheres is 0.035, the rare earth elements in the rare earth chloride are lanthanum and cerium, calculated as lanthanum oxide and cerium oxide, the mass ratio of lanthanum oxide and cerium oxide in the rare earth chloride is 2:1, the total volume of water in the deionized water and rare earth chloride aqueous solution and the mass ratio of NaY zeolite crystallized microspheres is 4.3L / g), mixed evenly, adjusted to a pH value of 3.5, exchanged at 90°C for 1h, filtered and washed to obtain a "second exchange" wet cake, calcined at 650°C for 2h to obtain a primary rare earth exchange microsphere, and water and a rare earth chloride aqueous solution were added to the primary rare earth exchange microspheres. The solution (the concentration of rare earth oxide in the rare earth chloride aqueous solution is 265g / L, the mass ratio of rare earth oxide to NaY zeolite crystallized microspheres is 0.05, the rare earth elements in the rare earth chloride are lanthanum and cerium, calculated as lanthanum oxide and cerium oxide, the mass ratio of lanthanum oxide to cerium oxide in the rare earth chloride is 2:1, the total volume of deionized water and water in the rare earth chloride aqueous solution and the mass ratio of NaY zeolite crystallized microspheres is 5L / g), mixed evenly, adjusted to pH 3.0, exchanged at 90℃ for 1.5h, filtered and washed to obtain a "three-cross" wet cake, and heated at 580 ℃ calcined for 1.5h to obtain secondary rare earth exchange microspheres; 4500g water and 90g ammonium dihydrogen phosphate (the mass ratio of ammonium dihydrogen phosphate to NaY zeolite crystallized microspheres is 0.09, and the mass ratio of the volume of water to the NaY zeolite crystallized microspheres is 4.5L / g) were added to the secondary rare earth exchange microspheres, mixed evenly, the pH value was adjusted to 3.5, modified at 95℃ for 1h, filtered, washed and dried to obtain a high-stability in-situ crystallized catalyst, recorded as HC-3, and the rare earth oxide content was 6.7wt% and P1.8wt% after analysis.

[0142] Example 6 The preparation method of the high-stability in-situ crystallization catalyst is as follows: (1) 5000 g of halloysite (calcined), orthophosphoric acid, water glass, silica-alumina activator SA-3 and water (the mass ratio of halloysite to orthophosphoric acid, water glass and silica-alumina activator SA-3 is 100:1.5:3:12, and the mass ratio of the mass of halloysite, the total mass of orthophosphoric acid and water glass to the silica-alumina activator SA-3 is 100:4.5:12) are prepared into a kaolin slurry with a solid content of 38%, and spray-dried to obtain 4500 g of kaolin microspheres with a main particle size of 20-150 μm, which are recorded as RM3; (2) The kaolin microspheres were calcined at 990°C for 1 h to obtain kaolin microspheres, which were designated as GM3-2. The kaolin microspheres were calcined at 810°C for 2 h to obtain PM3-2. (3) Mix the high-quality zeolite balls and the partial zeolite balls with water, water glass, sodium hydroxide solution (Na2O 16wt%), 2# seed crystals and alumina-silica activator SA-2 (the mass ratio of the high-quality zeolite balls and the partial zeolite balls is 1:4, and the mass ratio of the total mass of the high-quality zeolite balls and the partial zeolite balls, water glass, sodium hydroxide solution, 2# seed crystals, alumina-silica activator SA-2 and water is 100:330:250:3.8:85:40), and perform in-situ crystallization synthesis reaction at 98°C for 26h, filter, wash and dry to obtain NaY zeolite crystallized microspheres, recorded as JM-6; (4) 1000 g of NaY zeolite crystallized microspheres, 350 g of ammonium nitrate and 4500 g of deionized water were mixed (the mass ratio of ammonium nitrate to NaY zeolite crystallized microspheres was 0.35, and the volume ratio of water to the mass ratio of NaY zeolite crystallized microspheres was 4.5 L / g), the pH value was adjusted to 3.0, exchanged at 85 °C for 2 h, filtered and washed to obtain a "one-cross" filter cake; deionized water and rare earth chloride aqueous solution (the concentration of rare earth oxides in the rare earth chloride aqueous solution was 265 g / L, and the concentration of rare earth oxides in the rare earth chloride aqueous solution was 265 g / L, and the concentration of rare earth oxides in the rare earth chloride aqueous solution was 265 g / L) were added to the "one-cross" filter cake. The mass ratio of oxide to NaY zeolite crystallized microspheres is 0.035, the rare earth elements in rare earth chloride are lanthanum and cerium, and the mass ratio of lanthanum oxide to cerium oxide in rare earth chloride is 2:1, and the mass ratio of the total volume of water in deionized water and rare earth chloride aqueous solution to NaY zeolite crystallized microspheres is 4.3L / g), mixed evenly, adjusted to pH 3.5, exchanged at 90°C for 1h, filtered and washed to obtain a "second exchange" wet cake, which was calcined at 650°C for 2h to obtain a primary rare earth exchange microsphere. Water and rare earth chloride aqueous solution (the concentration of rare earth oxide in the rare earth chloride aqueous solution is 265 g / L, the mass ratio of rare earth oxide to NaY zeolite crystallized microspheres is 0.05, the rare earth elements in the rare earth chloride are lanthanum and cerium, calculated as lanthanum oxide and cerium oxide, the mass ratio of lanthanum oxide to cerium oxide in the rare earth chloride is 2:1, the total volume of deionized water and water in the rare earth chloride aqueous solution and the mass ratio of NaY zeolite crystallized microspheres is 5 L / g) were added to the primary rare earth exchange microspheres, mixed evenly, and the pH value was adjusted to 3.0, 9 Exchange at 0℃ for 1.5h, filter and wash to obtain a "three-cross" wet cake, which is calcined at 580℃ for 1.5h to obtain secondary rare earth exchange microspheres; add water and 90g of diammonium phosphate (the mass ratio of diammonium phosphate to NaY zeolite crystallized microspheres is 0.09, and the mass ratio of the volume of water to the NaY zeolite crystallized microspheres is 4.5L / g) to the secondary rare earth exchange microspheres, mix well, adjust the pH value to 3.5, modify at 95℃ for 1h, filter, wash and dry to obtain a high-stability in-situ crystallization catalyst.

[0143] Example 7 The preparation method of the high-stability in-situ crystallization catalyst is as follows: (1) 2500 g of halloysite (calcined base), 2500 g of kaolin (calcined base), polyacrylamide, water glass, silica-alumina activator SA-3 and water (the mass ratio of the total mass of halloysite and kaolin to the mass of polyacrylamide, water glass and silica-alumina activator SA-3 is 100:2:6:8, and the mass ratio of the total mass of halloysite and kaolin, the total mass of polyacrylamide and water glass to the silica-alumina activator SA-3 is 100:8:8) are prepared into a kaolin slurry with a solid content of 40%, and spray-dried to obtain 4400 g of kaolin microspheres with a main particle size of 20-150 μm, which are recorded as RM4; (2) The kaolin microspheres were calcined at 930°C for 3 h to obtain kaolin microspheres, which were recorded as GM4-1; the kaolin microspheres were calcined at 750°C for 3.5 h to obtain PM4-1; (3) Mix the kaolinite balls and the zeolite balls with water, water glass, sodium hydroxide solution (Na2O 16wt%), 1# seed crystals and alumina-silica activator SA-3 (the mass ratio of the kaolinite balls and the zeolite balls is 3.3:6.7, and the mass ratio of the total mass of the kaolinite balls and the zeolite balls, water glass, sodium hydroxide solution, 1# seed crystals, alumina-silica activator SA-3 and water is 100:320:230:4.5:78:50), and perform in-situ crystallization synthesis reaction at 98°C for 28h, filter, wash and dry to obtain NaY zeolite crystallized microspheres, recorded as JM-7; (4) Mix 1000 g of NaY zeolite crystallized microspheres, 550 g of ammonium chloride and 5500 g of deionized water (the mass ratio of ammonium chloride to NaY zeolite crystallized microspheres is 0.55, and the volume ratio of water to the mass ratio of NaY zeolite crystallized microspheres is 5.5 L / g), adjust the pH value to 3.2, exchange at 90 °C for 2 h, filter and wash to obtain a "one-cross" filter cake; add deionized water and rare earth chloride aqueous solution (the concentration of rare earth oxides in the rare earth chloride aqueous solution is 265 g / L, and the concentration of rare earth oxides and NaY zeolite is 265 g / L) to the "one-cross" filter cake. The mass ratio of the crystallized microspheres is 0.055, the rare earth elements in the rare earth chloride are lanthanum and cerium, and the mass ratio of lanthanum oxide to cerium oxide in the rare earth chloride is 2:1, and the total volume of water in the deionized water and rare earth chloride aqueous solution and the mass ratio of the NaY zeolite crystallized microspheres is 5.3L / g), mixed evenly, adjusted to a pH value of 3.2, exchanged at 90°C for 1.5h, filtered and washed to obtain a "second exchange" wet cake, calcined at 550°C for 3h to obtain a primary rare earth exchange microsphere, and water and rare earth chloride were added to the primary rare earth exchange microspheres. The rare earth solution (the concentration of rare earth oxide in the rare earth chloride aqueous solution is 265g / L, the mass ratio of rare earth oxide to NaY zeolite crystallized microspheres is 0.035, the rare earth elements in the rare earth chloride are lanthanum and cerium, calculated as lanthanum oxide and cerium oxide, the mass ratio of lanthanum oxide to cerium oxide in the rare earth chloride is 2:1, the total volume of deionized water and water in the rare earth chloride aqueous solution and the mass ratio of NaY zeolite crystallized microspheres is 4.5L / g), mixed evenly, adjusted the pH value to 3.2, exchanged at 85℃ for 2h, filtered and washed to obtain a "three-cross" wet filter cake, The secondary rare earth exchange microspheres were calcined at 600°C for 1.5h. Water and 75g of ammonium dihydrogen phosphate were added to the secondary rare earth exchange microspheres (the mass ratio of ammonium dihydrogen phosphate to NaY zeolite crystallized microspheres was 0.075, and the mass ratio of the volume of water to the NaY zeolite crystallized microspheres was 6.5L / g), mixed evenly, the pH value was adjusted to 3, and the catalyst was modified at 90°C for 1.5h. The catalyst was filtered, washed and dried to obtain a highly stable in-situ crystallized catalyst, recorded as HC-4. The rare earth oxide contents were 4.6wt% and P1.3wt% respectively.

[0144] Example 8 The preparation method of the high-stability in-situ crystallization catalyst is as follows: (1) 2500 g of halloysite (calcined base), 2500 g of kaolin (calcined base), polyacrylamide, water glass, silica-alumina activator SA-3 and water (the mass ratio of the total mass of halloysite and kaolin to the mass of polyacrylamide, water glass and silica-alumina activator SA-3 is 100:2:6:8, and the mass ratio of the total mass of halloysite and kaolin, the total mass of polyacrylamide and water glass to the silica-alumina activator SA-3 is 100:8:8) are prepared into a kaolin slurry with a solid content of 40%, and spray-dried to obtain 4400 g of kaolin microspheres with a main particle size of 20-150 μm, which are recorded as RM4; (2) The kaolin microspheres were calcined at 970°C for 2 h to obtain kaolin microspheres, which were designated as GM4-2; the kaolin microspheres were calcined at 830°C for 2 h to obtain PM4-2; (3) Mix the kaolinite balls and the zeolite balls with water, water glass, sodium hydroxide solution (Na2O 16wt%), 1# seed crystals and alumina-silica activator SA-3 (the mass ratio of the kaolinite balls and the zeolite balls is 1:3, and the mass ratio of the total mass of the kaolinite balls and the zeolite balls, water glass, sodium hydroxide solution, 1# seed crystals, alumina-silica activator SA-3 and water is 100:270:210:4.4:79:40), and perform in-situ crystallization synthesis reaction at 98°C for 31h, filter, wash and dry to obtain NaY zeolite crystallized microspheres, recorded as JM-8; (4) 1000 g of NaY zeolite crystallized microspheres, 550 g of ammonium chloride and 5500 g of deionized water were mixed (the mass ratio of ammonium chloride to NaY zeolite crystallized microspheres was 0.55, and the volume ratio of water to the mass ratio of NaY zeolite crystallized microspheres was 5.5 L / g), the pH value was adjusted to 3.2, exchange was performed at 90°C for 2 h, and a "one-cross" filter cake was obtained after filtering and washing; deionized water and a rare earth chloride aqueous solution (the concentration of rare earth oxides in the rare earth chloride aqueous solution was 265 g / L, and the concentration of rare earth oxides in the rare earth chloride aqueous solution was 265 g / L) were added to the "one-cross" filter cake. The mass ratio of the rare earth chloride to the NaY zeolite crystallized microspheres is 0.055, the rare earth elements in the rare earth chloride are lanthanum and cerium, calculated as lanthanum oxide and cerium oxide, the mass ratio of lanthanum oxide to cerium oxide in the rare earth chloride is 2:1, the total volume of water in the deionized water and rare earth chloride aqueous solution and the mass ratio of the NaY zeolite crystallized microspheres is 5.3L / g), mixed evenly, adjusted to a pH value of 3.2, exchanged at 90°C for 1.5h, filtered and washed to obtain a "secondary exchange" wet cake, which was calcined at 550°C for 3h to obtain primary rare earth exchange microspheres. Add water and rare earth chloride aqueous solution to the primary rare earth exchange microspheres (the concentration of rare earth oxide in the rare earth chloride aqueous solution is 265 g / L, the mass ratio of rare earth oxide to NaY zeolite crystallized microspheres is 0.035, the rare earth elements in the rare earth chloride are lanthanum and cerium, calculated as lanthanum oxide and cerium oxide, the mass ratio of lanthanum oxide to cerium oxide in the rare earth chloride is 2:1, the total volume of deionized water and water in the rare earth chloride aqueous solution and the mass ratio of NaY zeolite crystallized microspheres is 4.5 L / g), mix well, and adjust the pH value to 3.2 , exchange at 85℃ for 2h, filter and wash to obtain a "three-cross" wet cake, which is calcined at 600℃ for 1.5h to obtain secondary rare earth exchange microspheres; add water and 75g of diammonium phosphate (the mass ratio of diammonium phosphate to NaY zeolite crystallized microspheres is 0.075, and the mass ratio of the volume of water to the NaY zeolite crystallized microspheres is 6.5L / g) to the secondary rare earth exchange microspheres), mix evenly, adjust the pH value to 3, modify at 90℃ for 1.5h, filter, wash and dry to obtain a high-stability in-situ crystallization catalyst.

[0145] Comparative Example 1 (1) According to Example 1 of patent CN1778676A, SM-1 kaolin spray balls were prepared, Example 4 was used to prepare calcined balls SC1-2 and SP1-2, and Example 7 used SC1-2 and SP1-2 to prepare crystallized microspheres DJM; (2) Mix 1000 g of crystallized microspheres DJM, 550 g of ammonium chloride and 5500 g of deionized water (the mass ratio of ammonium chloride to crystallized microspheres DJM is 0.55, and the mass ratio of the volume of water to the crystallized microspheres DJM is 5.5 L / g), adjust the pH value to 3.2, exchange at 90 °C for 2 h, filter and wash to obtain a "one-cross" filter cake; add deionized water and rare earth chloride aqueous solution (the concentration of rare earth oxides in the rare earth chloride aqueous solution is 265 g / L, and the mass ratio of rare earth oxides to crystallized microspheres DJM is 5.5 L / g) to the "one-cross" filter cake. The mass ratio of lanthanum oxide to cerium oxide in rare earth chloride is 2:1, and the mass ratio of the total volume of water in the deionized water and rare earth chloride aqueous solution to the crystallized microsphere DJM is 5.3L / g), mixed evenly, adjusted to pH 3.2, exchanged at 90℃ for 1.5h, filtered and washed to obtain a "second exchange" wet cake, calcined at 550℃ for 3h to obtain a primary rare earth exchange microsphere, and water and chlorine were added to the primary rare earth exchange microsphere. The rare earth chloride aqueous solution (the concentration of rare earth oxide in the rare earth chloride aqueous solution is 265g / L, the mass ratio of rare earth oxide to crystallized microspheres DJM is 0.035, the rare earth elements in the rare earth chloride are lanthanum and cerium, calculated as lanthanum oxide and cerium oxide, the mass ratio of lanthanum oxide to cerium oxide in the rare earth chloride is 2:1, the total volume of deionized water and water in the rare earth chloride aqueous solution and the mass ratio of crystallized microspheres DJM is 4.5L / g), mixed evenly, adjusted the pH value to 3.2, exchanged at 85℃ for 2h, filtered and washed, The "three-cross" wet filter cake was obtained and calcined at 600°C for 1.5h to obtain secondary rare earth exchange microspheres; water and 75g of diammonium phosphate were added to the secondary rare earth exchange microspheres (the mass ratio of diammonium phosphate to crystallized microspheres DJM was 0.075, and the mass ratio of the volume of water to the crystallized microspheres DJM was 6.5L / g), mixed evenly, the pH value was adjusted to 3, modified at 90°C for 1.5h, filtered, washed and dried to obtain a catalyst, recorded as DC, and the rare earth oxide content was measured to be 4.7wt% and P 1.4wt%.

[0146] The XRD pattern of NaY zeolite crystallized microspheres JM-7 prepared in step (3) of Example 7 is as follows: Figure 1 As shown, its SEM image is Figure 2 The SEM image of its surface is shown in Figure 3 shown.

[0147] The XRD pattern of the crystallized microsphere DJM prepared in step (1) of comparative example 1 is as follows: Figure 4As shown, its SEM image is as follows Figure 5 The SEM image of its surface is shown in Figure 6 shown.

[0148] The parameters of the in-situ crystallization synthesis reaction in Examples 1 to 8 and Comparative Example 1 and the crystallinity and silicon-aluminum ratio of the prepared crystallized microspheres are shown in Table 1.

[0149] Table 1 Parameters of in-situ crystallization synthesis reaction and crystallinity and silicon-aluminum ratio of prepared crystallized microspheres in Examples 1 to 8 and Comparative Example 1

[0150] It can be seen from Table 1 that the crystallized microspheres prepared by the present invention have higher crystallinity and higher silicon-aluminum ratio.

[0151] Metal contamination experiments were conducted on the catalysts prepared in Examples 1, 3, 5, 7 and Comparative Example 1 to compare and analyze the differences in their ability to resist metal contamination. HC-1 to HC-4 and DC catalysts were contaminated with V 8000ppm and Ni 4000ppm, respectively, and aged for 4 hours at 800°C and 100% steam; at the same time, the uncontaminated catalyst was aged for 17 hours at 800°C and 100% steam, and then the micro-reactivity of the aged catalysts was tested. The micro-activity data of the catalysts before and after metal contamination are listed in Table 2.

[0152] Table 2 Comparison of micro-reaction activity before and after metal contamination

[0153] It can be seen from Table 2 that, compared with the comparative catalyst DC, the catalyst of the present invention has higher micro-reaction activity and metal contamination activity retention rate.

[0154] Application Examples The reaction effects of the catalysts prepared in Examples 1, 3, 5, 7 and Comparative Example 1 of the present invention are described using a fixed fluidized bed reaction evaluation device. HC-1 to HC-4 and DC catalysts were treated at 800°C and 100% steam for 17 hours, and then cracked in an ACE (Advanced Catalytic Evaluation) fixed fluidized bed reactor. The reaction conditions were a catalyst loading of 9 g, a catalyst-to-oil ratio of 6, a reaction temperature of 527°C, and a weight space velocity of 8 h. -1 The properties of the raw oil are shown in Table 3, and the catalytic results are shown in Table 4.

[0155] Table 3 Properties of feedstock oil for ACE reaction

[0156] Table 4 Distribution of reaction products and catalyst performance in application examples

[0157] Total liquid intake refers to: liquefied gas + gasoline + diesel.

[0158] As can be seen from Table 4, compared with the comparative catalyst DC, the catalyst provided by the present invention has higher heavy oil conversion capacity and target product yield (total liquid yield, gasoline), showing excellent catalytic reaction performance.

[0159] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a high-stability in-situ crystallization catalyst, characterized in that: The following steps are involved: (1) Mixing kaolin with water, a silicon-aluminum activator and a dispersant, and spray drying to obtain kaolin microspheres; (2) subjecting part of the kaolin microspheres obtained in step (1) to a first calcination to obtain kaolin microspheres; (3) subjecting the remaining kaolin microspheres obtained in step (1) to a second calcination to obtain kaolin microspheres; (4) mixing the high-soil balls obtained in step (2) and the partial-soil balls obtained in step (3), water, a silicon source, a sodium hydroxide solution, a seed crystal and a silicon-alumina activator, and performing an in-situ crystallization synthesis reaction to obtain NaY zeolite crystallized microspheres; (5) mixing the NaY zeolite crystallized microspheres obtained in step (4) with ammonium salt and water to perform ammonium salt exchange to obtain ammonium salt exchange microspheres; (6) mixing the ammonium salt exchange microspheres obtained in step (5) with a rare earth salt and water, and sequentially performing a first rare earth exchange and a third calcination to obtain primary rare earth exchange microspheres; (7) mixing the primary rare earth exchange microspheres obtained in step (6) with rare earth salt and water, and sequentially performing a second rare earth exchange and a fourth calcination to obtain secondary rare earth exchange microspheres; (8) The secondary rare earth exchange microspheres obtained in step (7), water and a phosphorus compound or a boron compound are mixed and modified to obtain a high-stability in-situ crystallization catalyst.

2. The preparation method according to claim 1, characterized in that: In the step (1), the mass ratio of kaolin, silica-alumina activator and dispersant is 100:(0.5-12):(2-12).

3. The preparation method according to claim 1, characterized in that: In the step (2), the temperature of the first calcination is 900-1100° C., and the time of the first calcination is 0.5-5 h.

4. The preparation method according to claim 1, characterized in that: The temperature of the second roasting in step (3) is 700-880° C., and the time of the second roasting is 0.5-5 h.

5. The preparation method according to claim 1, characterized in that: The temperature of the in-situ crystallization synthesis reaction in step (4) is 90-110° C., and the time of the in-situ crystallization synthesis reaction is 16-40 hours.

6. The preparation method according to claim 1, characterized in that: In the step (5), the pH value of the ammonium salt exchange is 2.5-4, the temperature of the ammonium salt exchange is 30-100° C., and the time of the ammonium salt exchange is 0.5-4 h.

7. The preparation method according to claim 1, characterized in that: In the step (6), the pH value of the first rare earth exchange is 3-5, the temperature of the first rare earth exchange is 30-100° C., and the time of the first rare earth exchange is 0.5-4 h.

8. The preparation method according to claim 1, characterized in that: The pH value of the modification treatment in step (8) is 2.5-4, the temperature of the modification treatment is 40-100° C., and the time of the modification treatment is 0.5-4 h.

9. A high-stability in-situ crystallization catalyst prepared by the preparation method according to any one of claims 1 to 8.

10. Use of the high-stability in-situ crystallization catalyst according to claim 9 in heavy oil catalytic cracking.

Citation Information

Patent Citations

  • Method for preparing in situ crystallization type catalytic cracking catalyst

    CN101537368A

  • Preparation method of modified catalyst

    CN102921449A

  • Catalytic cracking catalyst for efficient conversion of heavy oil, and preparation method thereof

    CN103447063A

  • All-white clay catalyst for fluid catalytic cracking and its preparation

    CN1232862A

  • Ultra-stable rare earth y-type molecular sieve and preparation method therefor

    US20150151284A1

Cited By

  • NaY zeolite in-situ crystallization microsphere with high silica-alumina ratio as well as preparation method and application of NaY zeolite in-situ crystallization microsphere

    CN121405106A

  • A high-silicon-aluminum-ratio NaY zeolite in-situ crystallization microsphere, a preparation method and application thereof

    CN121405106B

  • NaY zeolite molecular sieve with high mesoporous volume as well as preparation method and application of NaY zeolite molecular sieve

    CN121823608A